2009
DOI: 10.1089/jir.2008.0095
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Trans-Signaling Regulates Glycogen Consumption Afterd-Galactosamine-Induced Liver Damage

Abstract: The cytokine interleukin-6 (IL-6) is important for liver regeneration. IL-6 can stimulate target cells either by binding to the membrane-bound IL-6 receptor (IL-6R) leading to dimerization and activation of gp130 or by binding to a soluble IL-6R that results in an activation of gp130 independently of membrane-bound IL-6R, a process called trans-signaling. We have established a transgenic mouse line, in which only trans-signaling is abrogated whereas signaling via the membrane-bound IL-6R is intact. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Findings from our in vitro studies of IL-6 trans signaling in fibroblasts are consistent with previous studies that have demonstrated that trans signaling can induce hepatocyte proliferation and intracellular signaling (73), promote collagen production in cardiac fibroblasts (42) and induce proliferation and extracellular matrix protein production in fibroblasts from hypertrophic scars (74). It must be noted, however, that Moodley et al examined the effect of IL-6 on fibroblast proliferation and concluded that IL-6 inhibits proliferation in normal fibroblasts but enhanced proliferation in IPF fibroblasts (75).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings from our in vitro studies of IL-6 trans signaling in fibroblasts are consistent with previous studies that have demonstrated that trans signaling can induce hepatocyte proliferation and intracellular signaling (73), promote collagen production in cardiac fibroblasts (42) and induce proliferation and extracellular matrix protein production in fibroblasts from hypertrophic scars (74). It must be noted, however, that Moodley et al examined the effect of IL-6 on fibroblast proliferation and concluded that IL-6 inhibits proliferation in normal fibroblasts but enhanced proliferation in IPF fibroblasts (75).…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrated that neutralization of IL-6 trans signaling resulted in a reduction in fibroblasts (data not shown) and myofibroblast accumulation and extracellular matrix protein production and deposition in the lungs, which translated to a reduction in pulmonary fibrosis and improvement in pulmonary oxygenation. Previous studies have suggested a role for IL-6 trans signaling in liver fibrosis (73), renal fibrosis (41) and myocardial fibrosis (42), though none have demonstrated improvement in fibrosis with blockade of trans signaling. This is the first study to examine the role of IL-6 trans signaling in pulmonary fibrosis and demonstrated a therapeutic benefit to antagonism of this pathway in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration, however, was decreased in sgp130Fc transgenic mice. Moreover, early STAT3 phosphorylation, SOCS3 expression and glycogen consumption within the liver was dependent on IL-6 trans-signaling [61]. These data suggest that an activation of the IL-6 trans-signaling pathway via Hyper-IL-6 could be of therapeutic benefit for the treatment for FHF.…”
Section: Animal Models Simulating Different Pathological Liver Diseasesmentioning
confidence: 79%
“…And indeed, a very recent report demonstrated that blockade of IL-6 trans-signaling impaired the recruitment of inflammatory macrophages to white adipose tissue under a HFD, while it did not alter insulin resistance in that model [68]. Furthermore, glycogen consumption and synthesis in hepatocytes was regulated by IL-6 trans-signaling in two different models of liver damage [44,45].…”
Section: Key Pointmentioning
confidence: 90%
“…In these sgp130Fc transgenic mice, the response to D-galactosamine induced liver damage was shown to be compromised. Interestingly, the liver damage-induced glycogen consumption in the liver of the transgenic mice was strongly reduced indicating that glycogen consumption depended on IL-6 trans-signaling [44]. Upon acute CCl 4 damage, blockade of IL-6 transsignaling led to higher liver damage and to reduced refilling of hepatocyte glycogen stores [45].…”
Section: Reviewmentioning
confidence: 97%